LOKKO’ TRADITION IN ISLAMIC LAW PERSPECTIVE AND ITS IMPACT ON PATAMPANUA SOCIETY IN POLEWALI MANDAR REGENCY - Sadat, Anwar (Journal of Islam and Science, 2015)
Humans have been predetermined as social beings for the reason that in meeting their needs they have to interact with others. Accordingly, humans tend to live in groups and society. These groups then agreed to set up rules to deal with the attitudes and behaviors in their environments. These rules later on developed into principles, guidelines, and way of life of a society to be kept hold of by each individual in the community. The worldview of a community greatly influence the behavior of individuals living in that community environment, hence an individual intending to get along and survive in a particular group of people should be able to comprehend and get familiar with the custom, worldview, and norms applied in the pertinent society.